1983
DOI: 10.1111/j.1600-051x.1983.tb01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentine hypersensitivity ‐ A review

Abstract: A large number of compounds have been employed in the management of dentine hypersensitivity. The symptomatic nature of the condition and its variability poses many problems to any evaluation of effect. Several semi-quantitative methods of response have been used; however, at this time it is uncertain what advantages they hold over the patients' subjective assessment of improvement. A review of the clinical studies reveals that a positive result for every agent tested to date may be found. Nevertheless conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(83 citation statements)
references
References 61 publications
(73 reference statements)
0
78
2
3
Order By: Relevance
“…Thuy et al showed co-presence of appropriate levels of fluoride and strontium showed synergistic effects in remineralizing artificial enamel lesions [21]. These findings are the foundation of using strontium salts in remineralizing tooth paste [22,23].…”
Section: Introductionmentioning
confidence: 92%
“…Thuy et al showed co-presence of appropriate levels of fluoride and strontium showed synergistic effects in remineralizing artificial enamel lesions [21]. These findings are the foundation of using strontium salts in remineralizing tooth paste [22,23].…”
Section: Introductionmentioning
confidence: 92%
“…Dentin hypersensitivity has been defined as the pain arising from exposed dentin, typically in response to chemical, thermal, tactile or osmotic stimuli that cannot be explained as arising from any other form of dental defect or pathology [13]. Tooth hypersensitivity can fit the criteria of several pain terms as described by Merskey [14] for the International Association for the Study of Pain.…”
Section: Pain Mechanismsmentioning
confidence: 99%
“…At a clinical level, even with magnification, sensitive dentin looks the same as non-sensitive dentin. There is little to indicate that hypersensitive dentin differs in any way from normal dentin and the pain mechanisms are probably the same [13]. The term “dentin hypersensitivity” can be questioned, with perhaps “dentin sensitivity” being a more accurate description.…”
Section: Pain Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Klinik olarak %0.4 lük kalay fluorür uygulamasının %0.717'lik sulandırılmış fluor çözeltisiyle birlikte kullanılmasının 5 dk gibi kısa bir sürede dentin hassasiyetini giderebildiği bildirilmiştir. 45 Ayrıca SEM çalışmalarında kalay fluorür açığa çıkmış dentin yüzeylerinde çözül-meyen kristaller oluşturduğu bildirilmiştir.…”
Section: Kalay Fluorürunclassified